Variety seeking in the Singapore service industry. - Long, Zhenjie. (2008)
This exploratory research looks at whether consumers display higher variety seeking tendencies in low involvement services (versus high involvement); services with hedonic elements (versus utilitarian services); hybrid services (versus non-hybrid services); standardized services (versus customized services); informal service relationship (versus formal service relationship); and services with low customer contact (versus high customer contact).